Effect of surface charge density on the ice recrystallization inhibition activity of nanocelluloses. (15th April 2020) - Li, Teng; Zhong, Qixin; Zhao, Bin; Lenaghan, Scott; Wang, Siqun; Wu, Tao
Graphical abstract: Highlights: Nanocelluloses with similar DP or fibril lengths but varied SCDs were prepared. The IRI activity of nanocelluloses was determined by a "splat" assay. Decreasing SCD enhanced the IRI activity until fibril aggregation occurred. The enhanced IRI activity was associated with increased hydrophobicity. Low SCD CNCs were active in 40 % sucrose solution and high annealing temperatures. Abstract: Recently nanocelluloses have been found to possess ice recrystallization inhibition (IRI) activity, which have several potential applications. The present study focuses on the relationship between the surface charge density (SCD) of nanocelluloses and IRI activity. Cellulose nanocrystals (CNCs) and 2, 2, 6, 6-tetramethylpiperidine-1-oxyl oxidized cellulose nanofibrils (TEMPO-CNFs) with similar degrees of polymerization (DP) or fibril lengths but with different SCDs were prepared and characterized for IRI activity. When the SCD of CNCs was progressively reduced, an initial increase of IRI activity was observed, followed by a decrease due to fibril aggregation. CNCs with a low SCD became IRI active at increased unfrozen water fractions and higher annealing temperatures. TEMPO-CNFs with a low SCD also had higher IRI activity. Additionally, lowering pH to protonate the carboxylate groups of TEMPO-CNFs enhanced the IRI activity. These research findings are important in producing nanocelluloses with enhanced IRI activity and understanding their structure-activity relationship.